Observing offenders: incident reports by surveillance detectives, uniformed police, and civilians - Vredeveldt, Annelies (Legal and criminological psychology, 2017)
Purpose. Police officers often write reports about witnessed incidents, which may serve as evidence in court. We examined whether incident reports and identifications by police officers, and in particular specialized detectives on surveillance teams, are more complete or more accurate than reports and identifications by civilian observers. Methods. Our sample included 46 civilians, 52 uniformed police officers, and 42 surveillance detectives. Participants viewed a 15-min video of a drug transaction and were allowed to take notes while watching. Before viewing the video, all participants received a priority list of information considered most relevant to the police investigation, which had been constructed by an expert panel. Subsequently, participants completed a questionnaire addressing different types of crime-relevant information in the incident. They also viewed target-present and target-absent lineups: Two for persons central to the drug transaction and one for a background detail. Results. Reports of uniformed police officers and detectives on surveillance teams were significantly more complete than reports of civilians, particularly for the top-three priorities of crime-relevant information. Moreover, reports by detectives were significantly more accurate than reports by uniformed police officers and civilians. Detectives were also significantly more likely to identify the persons from the lineup, whereas civilians were significantly more likely to identify the background detail. Conclusions. Our findings demonstrate that police officers, and in particular specialized detectives on surveillance teams, are more observant of the crime-relevant aspects of an incident than civilian observers. Theoretical and practical implications are discussed.